Self Organizing Map Protocol for Expanding Heterogeneous Wireless Sensor Network for Single and Multiple Data Sink - Jitendra Bahadur Singh, R. C. Tripathi (International Journal of Advanced Science and Technology, 2020)
A bulky no. of sensor nodes with restricted energy resources are made up of WSN. A key problem in wireless sensor networks is, as energy is low, how sensitive information is collected in an energy capable method. The combination algorithm is a technique for reducing energy consumption that relies heavily on the efficiency of the Wireless Sensor Networks. Nevertheless, the key issue is choosing the best CH to speed up the network service. To date, further work has been conducted to solve this problem by considering various constraints. This article seeks to develop a novel clustering model with the best selection for the cluster head by considering 4 main benchmarks such as energy, distance delay, & protection. This paper is designed to refine the CH selection process using the parameters of enduring energy, sink distance & nodes density. Also, the multiple data sinks (MS-SOMOC) is being introduced, to deal with the hot-spot dilemma and minimize contact distance from nodes to sinks. Finally, in terms of the no. of alive nodes, n/w capacity, reliability, performance and remaining capacity of network, compare the proposed work to other traditional models.